Correction:Nucleocapsid (N) Gene Mutations of SARS-CoV-2 Can Affect Real-Time RT-PCR Diagnostic and Impact False-Negative Results(Viruses, (2021), 13, (2474), 10.3390/v13122474) - Lesbon, Jéssika Cristina Chagas; Poleti, Mirele Daiana; de Mattos Oliveira, Elisângela Chicaroni; Patané, José Salvatore Leister; Clemente, Luan Gaspar; Viala, Vincent Louis; Ribeiro, Gabriela; Giovanetti, Marta; de Alcantara, Luiz Carlos Junior; Teixeira, Olivia; Nonato, Maria Cristina; de Lima, Loyze Paola Oliveira; et al. (MDPI, 2022)
The authors hereby request the inclusion of two authors (Olivia Teixeira and Maria Cristina Nonato) in the recently published article in Viruses entitled “Nucleocapsid (N) gene mutations of SARS-CoV-2 can affect real-time RT-PCR diagnostic and impact false-negative results” [1].